(untitled) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2019)
The attention paid in the last twenty years to the judicial practices of Italian municipalities has proved to be still too tied to the previous historiography of law. this approach has produced an image of the practice reflected by the statutory rules, which only partially reflects the actual progress of the procedures. the rich series of libri condemnationum et inquisitionum, prepared by the vercelli court, thus represents a unique possibility of enriching the current knowledge on the penal procedure of the late fourteenth century and on the statutory incidence in the process dynamics. On the basis of the deeds drawn up by notaries in court, it was possible to suggest a schematization of the accusatory and inquisitorial practices, not otherwise identifiable due to the absence of specific provisions within the municipal statutes. the collation between heterogeneous sources also allowed a first definition of the procedural timescales, not completely identifiable by the inquisitorial registers alone, often without indications on the sentences issued. Furthermore, thanks to the dialogue between convictions and statutory norms, an evaluation was carried out on the weight of bans and private peaces, close among the parties in extra-judicial terms, on the economy of the process. Finally, the degree of influence of the dominant Milan on the various procedural outcomes was assessed. DOI 10.17464/9788867743315